Combining the Seed Endophytic Bacteria and the Back to the Future Approaches for Plant Holonbiont Breeding - L'Hoir, Maïwenn; Duponnois, Robin (Frontiers in Agronomy, 2021)
Given the limits of intensive agriculture (pollution, degradation of biodiversity or soil desertification), it is necessary to develop sustainable alternatives to respond to future agricultural demand. Among these sustainable alternatives is the use of microbial biostimulants. Despite convincing scientific studies on them, their agricultural use remains minor. This can be explained by the lack of efficiency and reliability of their use. This review proposes to develop efficient microbial biostimulants based on the combination of two approaches, namely that of endophytic bacteria from seeds and the Back to the Future approach. Seed endophytic bacteria have a major agroindustrial potential insofar as they stand out from other microbial agents by their resistance, competitiveness, efficiency and vertical transmission. Contrary to modern cultivars, non-domesticated plants harbor microbiomes which have not been impacted by the processes of domestication and agriculture intensification. The Back to the Future suggests therefore to use interesting microorganisms isolated from non-domesticated plants and to integrate them into modern cultivars. This could result in the rehabilitation of modern microbiomes and lead to make crop cultures more resistant and resilient. The idea consisting in the combination of both approaches aims at obtaining optimized microbiomes. Particular emphasis is placed on integrating these innovative microbiomes into variety breeding programs. Indeed, given the importance of plant-microorganism interactions, particularly from an agronomic point of view, taking the hologenome into account as a unit of selection in breeding programs is essential. This integrative and unprecedented approach to designing breeding programs is promising with a view to reconciling productivity and preservation of agroecosystems.